ASSESSMENT OF MANDIBULAR FRACTURES COMPLICATION RATES IN TWO EMERGENCY CENTERS FROM NORTH-EASTERN AND WESTERN ROMANIA - Ștefan Gherasimescu; Mihai-Liviu Ciofu; Petrică-Florin Sava; Silviu-Cătălin Tibeică; Daniela Șulea; Anca-Irina Grădinariu; Bianca-Andreea Onofrei; Andrei-Mihail Roșu; Carmen-Gabriela Stelea; Otilia Boișteanu; Marius-Octavian Pricop; Victor-Vlad Costan (Romanian Society of Oral Rehabilitation, 2023)
Aim of the study. The aim of the study was to determine the rate of suppurative complications that occur as a result of mandibular fractures and the factors that favor them. Material and methods. The rate of complications of mandibular fractures hospitalized in the Oral and Maxillofacial Surgery Clinic of the Clinical Emergency Hospital "Sf. Spiridon" Iasi, Romania and in the Oral and Maxillofacial Surgery Clinic of the Clinical Municipal Emergency Hospital Timisoara, was determined using different criteria such as: age, sex, origin, time elapsed from trauma to treatment, type of mandibular fracture, etiology, postoperative complications, and treatment. Results. From 2015 until 2021, there were registered in the Oral and Maxillofacial Surgery Clinic of the "St. Spiridon" Hospital Iasi, Romania, 1128 cases with mandibular fractures, 67 of which were complicated by suppurative processes. Also, between the same years, in the Oral and Maxillofacial Surgery Clinic of the Clinical Municipal Emergency Hospital Timisoara, there were 56 cases registered with mandibular fractures, with 9 suppurative complication cases. The location most frequently interested in suppurative complications was represented by the mandibular angle and followed by fracture with paramedian and lateral location. Conclusions. In suppurative complications, a major role is played by the location of the fracture, the degree of oral hygiene and not necessarily the period between the time of trauma and the diagnosis of the fracture.